LIVING ARRANGEMENT AND HOMEOWNERSHIP IMPACTS ON FERTILITY INTENTION TO ACHIEVE THE SUSTAINABLE DEVELOPMENT GOALS - Salamah, Umi; Samosir, Omas B.; Djutaharta, Triasih (Journal of Environmental Science and Sustainable Development, 2023)
A reduction in fertility is among the sustainable development goal indicators in Indonesia. This study analyzed the relationship between living arrangements and home ownership with fertility intention in Indonesia. The inferential analysis used in this study is ordinal logistic regression. The data used in this study came from the National Socioeconomic Survey 2017 results. The unit analysis in this study was women aged 15-49 years who were married and not contracepting. The dependent variable in this study was the fertility intention. The independent variables, namely living arrangement and home ownership, and the control variables, namely women's age, women's education, women's working status, parity, husband's education, husband's working status, living area, household income, grandparent's age, grandparent's health status, grandparent's working status, and grandparent's gender. This study was divided into three models. In the first model, women who live with their parents have 1.17 times higher tendency to have high fertility intentions than those with low fertility intentions or do not have fertility intentions than women who do not live with their parents. In the third model, women who live with their parents have 1.11 times higher tendency to have high fertility intentions than those who have low fertility intentions or do not have fertility intentions compared to women who do not live with their parents. The study results show that women who lived with their parents had higher odds of having high fertility intention. Women who lived in homes that were not their own tended to have high fertility intentions. From these results, it is hoped that there will be programs from the government for the elderly family so that the presence of parents or inlaws in the household can improve the quality of children more than the number of children.